1994
DOI: 10.1111/j.1467-8470.1994.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Systems and Human Impact at Cobrico Crater, South‐western Victoria

Abstract: This study assesses human impact on the landscape around Cobrico, a volcanic crater lake in dairying country in south‐western Victoria. It compares the last 150 years of impact of European settlement against approximately the previous 1500 years of prehistoric occupation and land use. Focus is on vegetation dynamics, erosion, productivity changes and the fire regime. Since European settlement there has been woodland clearance and recovery, the introduction of many plant and animal species and a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…At the nearby Cobrico Crater, Dodson et al (1994) also found little change in the rst 30 years of European settlement.…”
Section: Post-european Environmental Changementioning
confidence: 89%
“…At the nearby Cobrico Crater, Dodson et al (1994) also found little change in the rst 30 years of European settlement.…”
Section: Post-european Environmental Changementioning
confidence: 89%
“…, citing Orchard's (1985) seminal work on the genus, interpreted similar recent increases in Myriophyllum pollen as evidence of mass-flowering following stranding of Myriophyllum beds. Arguably, similar patterns at other lakes from the region (Tower Hill, main lake, zone ML1;Cobrico Crater, central core;Dodson et al 2004) imply that recent changes in the aquatic flora are perhaps indicative of some regional phenomenon, rather than site-specific variability in terra australis 34…”
Section: Vegetation Response To Holocene Climate Variability and Euromentioning
confidence: 92%
“…Palaeoenvironmental methods have been applied by Wasson and Clark (1985), Clark (1990), Boon and Dodson (1992) and Dodson et al (1993;1994a;1994b) to determine recent human impact on selected Australian environmental systems. This work is based on the approaches defined and used by Oldfield and Engstrom (Oldfield 1977;Oldfield 1983;Oldfield & Clark 1990;Engstrom & Wright 1984), among others.…”
Section: Introductionmentioning
confidence: 99%